2020
DOI: 10.1002/jclp.23030
|View full text |Cite
|
Sign up to set email alerts
|

Client and therapist agreement in moment‐to‐moment helpfulness ratings in psychotherapy: A microprocess approach

Abstract: Method: Clients (n = 16; M age = 32.88 years; 81% female) and their therapists (n = 10; 80% female) from a training clinic provided moment-to-moment ratings while reviewing a video recording of a recent session. West and Kenny's Truth-and-Bias (T&B) model was used to examine agreement in ratings. Multilevel modeling was used to evaluate the agreementalliance association while controlling for sessions completed. Results: Consistent with the T&B model, client-therapist ratings were temporally congruent and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…These results are consistent with another study conducted in the mental health inpatient setting where physician ratings were higher than those of patients (Beaudette et al, 2020). However, in the community setting, the opposite has been found, with higher scores assigned by patients compared to therapists (Andrade‐González et al, 2017; Hartmann et al, 2015; Igra et al, 2020; Penix et al, 2021). These differences could be attributed to the specific care environment under examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with another study conducted in the mental health inpatient setting where physician ratings were higher than those of patients (Beaudette et al, 2020). However, in the community setting, the opposite has been found, with higher scores assigned by patients compared to therapists (Andrade‐González et al, 2017; Hartmann et al, 2015; Igra et al, 2020; Penix et al, 2021). These differences could be attributed to the specific care environment under examination.…”
Section: Discussionmentioning
confidence: 99%
“…However, the existing clinical support tools are not always effective for restoring the therapeutic alliance and leading patients to improved outcomes (Coelho et al, 2021; Lambert et al, 2018). Therefore, it is important to understand the perspective of professionals and patients in order to analyse their agreements and disagreements regarding the TR (Beaudette et al, 2020; Flückiger et al, 2018; Igra et al, 2020; Lessard‐Deschênes & Goulet, 2022; Penix et al, 2021; Tschuschke et al, 2020). Although the TR may be experienced differently by the participants (Atzil‐Slonim et al, 2015; Hartmann et al, 2015; Kivlighan et al, 2016), the literature highlights that the agreement between professionals' and patients' estimates of the TR is fundamental in the assessment and outcomes of the care process (Hartmann et al, 2015; Igra et al, 2020; Lessard‐Deschênes & Goulet, 2022; Tschuschke et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some researchers have begun to use technological advances to gain a more detailed understanding of patients' beliefs about helpful and hindering aspects of psychotherapy. In one approach, patients are asked to simultaneously observe a video recording of a recent psychotherapy session and provide momentby-moment ratings of its helpfulness (see Penix et al, 2021;. This method provides microprocess data illustrating exactly when changes in helpfulness have occurred.…”
Section: Patient Microprocess Researchmentioning
confidence: 99%
“…In examining the research on patients' perspectives in psychotherapy, one important theme that arises is the importance of patient and psychotherapist convergence. For example, in the patient microprocesses paradigm, patient and psychotherapist convergences in moment-by-moment ratings have been found to significantly predict patient ratings of the therapeutic alliance (Penix et al, 2021). In addition, several studies have suggested that patient and psychotherapist convergence in ratings of process variables, such as the therapeutic alliance or outcome expectation, is linked to more positive psychotherapy outcomes (Bar-Kalifa et al, 2016;Coyne et al, 2018Coyne et al, , 2021Laws et al, 2017).…”
Section: The Importance Of Perspective Convergencementioning
confidence: 99%
“…Having clients code their own moment-to-moment behavior may help to identify and understand microprocesses (Wesselmann et al, 2012) with reduced recall bias (Penix et al, 2020). Other novel methods are being used to understand microprocesses in psychotherapy, such as helpfulness and hindrance (Penix et al, 2021; Swift et al, 2017). These studies suggest that clients and trainees can be trained in a brief way to reliably and accurately rate momentary helpfulness and hindrance during therapy sessions.…”
mentioning
confidence: 99%